2016
DOI: 10.1136/bmj.i276
|View full text |Cite
|
Sign up to set email alerts
|

Risk of invasive cervical cancer after atypical glandular cells in cervical screening: nationwide cohort study

Abstract: ObjeCtivesTo investigate the risks of invasive cervical cancer after detection of atypical glandular cells (AGC) during cervical screening.Design Nationwide population based cohort study.setting Cancer and population registries in Sweden.PartiCiPants 3 054 328 women living in Sweden at any time between 1 January 1980 and 1 July 2011 who had any record of cervical cytological testing at ages 23-59. Of these, 2 899 968 women had normal cytology results at the first screening record. The first recorded abnormal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 39 publications
2
51
0
1
Order By: Relevance
“…Therefore, they encounter early age pregnancies and excessive fertility problems. These problems increase the cervical cancer risk in the future (Kanbur & Capik, 2011;Guner & Taskiran, 2007;Kaya & Akin, 2009;Turkish Society of Gynecologic Oncology, 2017;American Cancer Society, 2017b, Ozgul, 2007Pinar et al, 2008;Lim et al, 2016;Wang et al, 2016;Niyazi et al, 2016). Pinar et al (2008) have found that 53.3% of the individuals with cervical cancer start their sexual intercourse at the age of 18 or younger.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, they encounter early age pregnancies and excessive fertility problems. These problems increase the cervical cancer risk in the future (Kanbur & Capik, 2011;Guner & Taskiran, 2007;Kaya & Akin, 2009;Turkish Society of Gynecologic Oncology, 2017;American Cancer Society, 2017b, Ozgul, 2007Pinar et al, 2008;Lim et al, 2016;Wang et al, 2016;Niyazi et al, 2016). Pinar et al (2008) have found that 53.3% of the individuals with cervical cancer start their sexual intercourse at the age of 18 or younger.…”
Section: Resultsmentioning
confidence: 99%
“…Cervical cancer increases with the number of pregnancies and births. It has been reported that the fact that the number of pregnancies is more than three, and having the first pregnancy and childbirth before the age of 20 are important risk factors for the cervical cancer (Kanbur & Capik, 2011;Guner & Taskiran 2007;Kaya & Akin, 2009;Turkish Society of Gynecologic Oncology, 2017;American Cancer Society, 2017b;Ozgul, 2007;Lim et al, 2016;Wang et al, 2016;Niyazi et al, 2016). In the study of Pinar et al (2008), it has been shown that the majority of individuals with cervical cancer have the first pregnancy at the age of 18 or younger (51.1%) and most of them have more than 3 children at this age (86.7%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…AIS is the only known precursor to cervical adenocarcinoma and, in many cases, invasive disease can be prevented with appropriate management [1]. The usual interval between clinically detectable adenocarcinoma in situ and early invasion is reportedly at least five years, which provides a wide scope for detection and intervention [2,3]. Glandular neoplasia in the uterine cervix is less common than squamous neoplasia, being the second most frequent histological type of lesion in the cervix.…”
Section: Introductionmentioning
confidence: 99%